Detection of Hb Constant Spring (HBA2: C.427T>C) Heterozygotes in Combination with β-Thalassemia or Hb e Trait by Capillary Electrophoresis - Sakorn Pornprasert (2018)
© 2015 © 2015 Informa Healthcare USA, Inc. All rights reserved: reproduction in whole or part not permitted. Hb Constant Spring (Hb CS; HBA2: c.427T>C) is often missed by routine laboratory testing as its mRNA as well as gene product are unstable and presented at a low level in peripheral blood. This study aimed to analyze the efficacy of capillary electrophoresis (CE) for detecting and quantifying of Hb CS in β-thalassemia (β-thal) trait or Hb E (HBB: c.79G>A) trait samples with reduced β-globin chain expression. Thalassemia diagnostic data were reviewed in 2524 blood samples that were submitted to the laboratory of the Associated Medical Sciences Clinical Service Center, Chiang Mai, Thailand for hemoglobinopathy and thalassemia diagnosis. DNA analysis for Hb CS was performed in 322 β-thal trait and 397 Hb E trait samples using the amplification refractory mutation system (ARMS). The CE electropherogram of Hb CS at zone 2 was observed in all five samples with β-thal trait and nine samples with Hb E trait with levels varying from 0.1-2.8 and 0.1-2.3%, respectively. Thus, the CE method proved useful for screening of Hb CS in samples with β-thal trait or Hb E trait, which is essential for providing accurate diagnosis, genetic counseling, prevention and control programs of Hb H-CS disease.